Personnel economics issues: What causes increasing work intensity, and what are the policy responses? - Dushko Josheski (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper the issue from personnel economics such as work intensity has been investigated. George Akerlof back in 1976 argued that the real life failed to correspond to the standard general equilibrium model set by Arrow-Debreu. In the real life information is neither complete nor it's costless. In real life workers tend to work in harsh conditions, and put more efforts in order to receive better wages, also they have incentives to educate themselves more, as better educated employees are more productive. More productive means that they work faster as the rat's race to the cheese and faster rats will get to the cheese first and get more cheese than slower rats. In reality workers do not want to share their output with slower workers. But it is because of bad norms that firms sets or taxes that government imposes that workers tend to work suboptimal i.e. work more than what is required in equilibrium, or work less than the equilibrium socially optimal required effort. The problem also arises when firms compare worker and pick `'average'' worker, nowadays in OECD (rich) countries club, workers tend to get paid more and get spurious data on increased productivity and the measure average effort to be biased, so wage function will then be biased w=w (ē, t), wage is function of average effort and time needed to produce output.
Keywords: M50; M51; M52; 330; Rat race equilibrium; labour market regulation policies; job satisfaction; workers performance